Staged Reconstruction (Delayed-Immediate) of the Maxillectomy Defect Using CAD/CAM Technology - Pang, John Henry; Brooke, Sebastian; Kubik, Mark W.; Ferris, Robert L.; Dhima, Matilda; Hanasono, Matthew M.; Wang, Eric W.; Solari, Mario G. (Journal of Reconstructive Microsurgery, 2018)
Background Computer-aided design/computer-aided manufacturing (CAD/CAM) technology has become increasingly popular for free fibula reconstruction of the mandible. The same technology, however, has not been widely utilized in immediate complex midface reconstruction utilizing free fibula flaps. Maxillary defects are difficult to precisely predict or produce matched cutting guides for after the ablative surgery. We present a protocol for “delayed-immediate” two-stage reconstruction for complex mid-facial defects, by delaying lymph node neck dissection and using CAD/CAM technology for delayed bony reconstruction.Methods Stage 1 includes the extirpative surgery, placement of a temporary obturator, and an immediate post-excision fine cut computed tomography (CT) of the defect that is used for CAD/CAM planning. The time interval between stages is used for virtual surgical planning (VSP) and provides an opportunity for the final pathologic margins to be evaluated. At stage 2, definitive reconstruction is performed in conjunction with the delayed neck dissection. Briefly delaying the neck dissection until stage 2 allows for recipient vessel dissection and microsurgical anastomoses to safely occur in a surgically naïve neck.Conclusion A two-stage delayed-immediate reconstruction of complex mid-face defects can be safely and effectively performed. This protocol takes advantage of advancing CAD/CAM technology, provides an opportunity to evaluate final margins, and avoids recipient vessel dissection and microsurgery in previously operated or irradiated necks.
Keywords: CAD/CAM; head and neck cancer; free fibula